2016
DOI: 10.21859/sija-1102226
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Lifestyle and Social Support with Marital Satisfaction of Elderly

Abstract: Objectives Given the improvement in the personal and social health level of elderly people, the present study aimed to investigate the relationship of factors like lifestyle and social support with marital satisfaction in elderly people in Iran. Methods & Materials The present study employed a cross-sectional descriptive correlation method. The study population included 381 elderly people aged 60 years and above. They were selected from health care centers using random cluster sampling technique. The subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…These developments enhance the marital relationship and prevent marital conflict, distress, and deterioration [26]. Our findings are consistent with Rafiee et al [27] results showing that lifestyle and perceived social support predict marital commitment in the elderly. Khodabakhshi et al [28] results also indicated a positive significant correlation between family, friends, and other people's perceived social support components and sexual satisfaction [28].…”
Section: Discussionsupporting
confidence: 92%
“…These developments enhance the marital relationship and prevent marital conflict, distress, and deterioration [26]. Our findings are consistent with Rafiee et al [27] results showing that lifestyle and perceived social support predict marital commitment in the elderly. Khodabakhshi et al [28] results also indicated a positive significant correlation between family, friends, and other people's perceived social support components and sexual satisfaction [28].…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the findings of other studies. In this regard, the results reported by Rafiee et al ( 2016) suggested a significant positive correlation between social support and marital satisfaction in the elderly [29]. Kavehfarsani and omidian also demonstrated a relationship between perceived social support and marital satisfaction [30].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, due to increasing aging phenomenon and the significant role of the elderly in society and the family through the transfer of experience, there is a need to pay attention to this group [6]. Marital satisfaction is one of the important issues in old age that can affect the quality of life [7]. Several factors can affect marital satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of physical state, increased chronic diseases in old age can be associated with adverse effects on marital satisfaction due to changes in roles and re-sponsibilities [16]; older peoples should accept new roles and replace them with previous ones. The new roles can change the psychological and physical components in them [7].…”
Section: Introductionmentioning
confidence: 99%